KINETICS OF THE LANGMUIRIAN ADSORPTION OF CUII IONS AT THE CALCITE WATER INTERFACE - Compton, R; Pritchard, K (1990)
A novel technique is presented which allows the kinetic parameters relating to the adsorption/desorption of copper(II) ions at the calcite/water interface to be determined. The new method utilises a double-channel electrode in which an Iceland Spar crystal forms part of one wall of the rectangular duct through which solution flows. Two copper electrodes are located immediately upstream and downstream of the crystal and flush with its surface. The downstream electrode is potentiostatted throughout the experiment at a value corresponding to the transport controlled reduction of CuII to Cuo. The potential of the upstream electrode is stepped from a value at which no current flows to one at which the electrode dissolves forming CuII, which then flows over the crystal to the detector electrode. Analysis of the current-time transient on this electrode permits the deduction of the adsorption/desorption kinetics of CuII at the crystal surface.